Menggagas Model Penerapan Prorogasi dalam Pemenuhan Asas Peradilan Sederhana, Cepat, dan Berbiaya Ringan - Abidin, Fikri Rafi Musyaffa; Taupiqqurrahman, Taupiqqurrahman (Universitas Semarang, 2024)
This research aims to initiate the revival of prorogation in civil procedural law in Indonesia and also design a relevant model to be implemented. In fact, all judicial processes in Indonesia must be guided by and apply the principles of simple, fast and low-cost justice. It is important to apply this principle in order to provide legal certainty in a short time and also make the courts an affordable means for all parties. However, in practice the civil justice process in Indonesia still tends to be slow and complicated, which often makes it difficult for justice seekers. The Supreme Court then created a simple claims institution to resolve cases where the value of the claim was not too large efficiently and reduce the flood of cases at the Supreme Court. However, simple lawsuits can only be used for certain cases so the scope of the case is very limited plus simple lawsuits are not able to significantly reduce the backlog of cases in the Supreme Court. So a solution is needed to overcome judicial problems in ordinary civil cases and also to reduce the backlog of cases at the Supreme Court. Prorogation, which is no longer practiced, can shorten the judicial process, which can then reduce the backlog of cases at the Supreme Court. This research is a type of normative juridical research carried out using the literature study method. The research results show that prorogation can be applied to realize simple, fast and low-cost justice in ordinary civil cases and can also reduce the backlog of cases at the Supreme Court. The application of prorogation in modern Indonesian civil procedural law requires several modifications to adapt to the needs and developments of the times. These modifications include simplifying the requirements for lawsuits and legal remedies as well as integrating e-court as a means of implementation. Penelitian ini bertujuan untuk menggagas penghidupan kembali prorogasi dalam hukum acara perdata di Indonesia dan juga merancang model yang ideal untuk diterapkan. Sejatinya seluruh proses peradilan di Indonesia harus berpedoman dan menerapkan prinsip peradilan yang sederhana, cepat, dan biaya ringan. Prinsip tersebut penting diterapkan guna memberikan kepastian hukum dalam waktu yang singkat dan juga menjadikan pengadilan sebagai sarana yang terjangkau bagi seluruh pihak. Namun, pada praktiknya proses peradilan perdata di Indonesia masih cenderung lamban dan berbelit-belit sehingga kerap kali menyulitkan para pencari keadilan. Mahkamah Agung kemudian membuat lembaga gugatan sederhana guna menyelesaikan perkara yang nilai gugatannya tidak terlalu besar dengan efisien dan mengurai banjir perkara di Mahkamah Agung. Namun, gugatan sederhana hanya dapat digunakan untuk perkara-perkara tertentu sehingga ruang lingkup perkaranya sangat terbatas, gugatan sederhana juga tidak mampu mengurai penumpukan perkara di Mahkamah Agung secara signifikan. Sehingga dibutuhkan solusi guna mengatasi masalah peradilan dalam perkara perdata biasa dan juga untuk mengurangi penumpukan perkara di Mahkamah Agung. Prorogasi yang sudah tidak lagi dipraktekan dapat mempersingkat proses peradilan, yang kemudian dapat menurunkan penumpukan perkara di Mahkamah Agung. Penelitian ini merupakan jenis penelitian yuridis normatif yang dilakukan dengan metode studi kepustakaan. Hasil penelitian menunjukan prorogasi dapat diterapkan guna mewujudkan peradilan sederhana, cepat, dan berbiaya ringan pada perkara perdata biasa dan juga dapat mengurai penumpukan perkara di Mahkamah Agung. Penerapan prorogasi dalam hukum acara perdata modern Indonesia memerlukan beberapa modifikasi guna menyesuaikan dengan kebutuhan dan perkembangan zaman yang ada. Modifikasi tersebut mencakup penyederhanaan persyaratan gugatan dan upaya hukum serta pengintegrasian e-court sebagai sarana pelaksana.